2014
DOI: 10.1093/jac/dku208
|View full text |Cite
|
Sign up to set email alerts
|

Incidence rates of carbapenemase-producing Enterobacteriaceae clinical isolates in France: a prospective nationwide study in 2011-12

Abstract: The incidence-density rate of carbapenemase-producing isolates per 1000 hospital-days was low and 30-fold lower than that of carbapenem-NS isolates (0.125) and almost 300-fold lower than that of ESBL-producing isolates (1.104) in these French hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 23 publications
2
35
1
1
Order By: Relevance
“…Only 2 of 139 strains produced ␤-lactamases (IMI-3 and OXA-48). These results are in agreement with previous studies, carried out in Chile (22), Korea (23), China (24), United Kingdom (25), Belgium (26), and France (5,27), which showed that the emergence of carbapenem resistance in Enterobacteriaceae could be supported mainly by the combination of ESBLs or AmpC ␤-lactamases with porin deficiency in certain areas. Recent reports highlighted the implication of carbapenemnonsusceptible noncarbapenemase producers in nosocomial outbreaks (28) in different countries, mostly from K. pneumoniae or Enterobacter spp.…”
Section: Discussionsupporting
confidence: 93%
“…Only 2 of 139 strains produced ␤-lactamases (IMI-3 and OXA-48). These results are in agreement with previous studies, carried out in Chile (22), Korea (23), China (24), United Kingdom (25), Belgium (26), and France (5,27), which showed that the emergence of carbapenem resistance in Enterobacteriaceae could be supported mainly by the combination of ESBLs or AmpC ␤-lactamases with porin deficiency in certain areas. Recent reports highlighted the implication of carbapenemnonsusceptible noncarbapenemase producers in nosocomial outbreaks (28) in different countries, mostly from K. pneumoniae or Enterobacter spp.…”
Section: Discussionsupporting
confidence: 93%
“…Also included are 13 isolates carrying MBLs and serine carbapenemases: VIM-1 and KPC-2 (n ϭ 4), IMP-4 and KPC-2 (n ϭ 2), VIM-4 and OXA-48 (n ϭ 2), VIM-31 and OXA-48 (n ϭ 1), NDM-1 and OXA-48 (n ϭ 3), and NDM-1 and OXA-232 (n ϭ 1). have been performed, and the frequency of noncarbapenemasemediated mechanisms among carbapenem-nonsusceptible Enterobacteriaceae has been found to be 77.2 to 98.6% (13,(32)(33)(34). These estimates exceeded the proportion observed here, but that is likely because those collections included ertapenem-nonsusceptible isolates, against which meropenem can retain some activity, whereas that was not the case in the present work (35).…”
contrasting
confidence: 64%
“…OXA-48 prevalence is also increasing in other European countries, such as France, Germany, Belgium, and the United Kingdom, where increasing numbers of outbreaks have been described (1,(17)(18)(19)(20)(21). However, OXA-48 is rarely identified in North America (22).…”
Section: Bacterial Isolates and Carbapenemase Typesmentioning
confidence: 99%